Factors affecting malnutrition in children and the uptake of interventions to prevent the condition. Issue 1 (December 2015) - Tette, Edem; Sifah, Eric; Nartey, Edmund
Abstract Background Malnutrition is a major cause of child morbidity and mortality. There are several interventions to prevent the condition but it is unclear how well they are taken up by both malnourished and well nourished children and their mothers and the extent to which this is influenced by socio-economic factors. We examined socio-economic factors, health outcomes and the uptake of interventions to prevent malnutrition by mothers of malnourished and well-nourished in under-fives attending Princess Marie Louise Children's Hospital (PML). Methods An unmatched case control study of malnourished and well-nourished children and their mothers was conducted at PML, the largest facility for managing malnutrition in Ghanaian children. Malnourished children with moderate and severe acute malnutrition were recruited and compared with a group of well-nourished children attending the hospital. Weight-for-height was used to classify nutritional status. Record forms and a semi-structured questionnaire were used for data collection, which was analysed with Stata 11.0 software. Results In all, 182 malnourished and 189 well-nourished children and their mothers/carers participated in the study. Children aged 6–12 months old formed more than half of the malnourished children. The socio-demographic factors associated with malnutrition in the multivariate analysis were age ≤24 months and a monthly family income of ≤200 GH Cedis. Whereas among the health outcomes, low birth weight, an episode of diarrhoea and the presence of developmental delay were associated with malnutrition. Among the interventions, inadequate antenatal visits, faltering growth and not de-worming one's child were associated with malnutrition in the multivariate analysis. Immunisation and Vitamin A supplementation were not associated with malnutrition. Missed opportunities for intervention were encountered. Conclusion Poverty remains an important underlying cause of malnutrition in children attending Princess Marie Louise Children's Hospital. Specific and targeted interventions are needed to address this and must include efforts to prevent low birthweight and diarrhoea, and reduce health inequalities. Regular antenatal clinic attendance, de-worming of children and growth monitoring should also be encouraged. However, further studies are needed on the timing and use of information on growth faltering to prevent severe forms of malnutrition.